Pemanfaatan Smart TV sebagai Sarana Transformasi Digital dalam Proses Pembelajaran untuk Meningkatkan Antusiasme dan Minat Baca Siswa Sekolah Dasar - Intan Maulidah; Rika Izzatun Nikmah; Muhammad Junaidi Retno Maggolo; Safira Diah Fitriyani; Nur Rohman (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2025)
The development of digital technology has had a significant impact on the world of education, one of which is the introduction of various new media in learning, such as Smart TV. Smart TV, with its interactive multimedia features, offers a great opportunity to improve the quality and effectiveness of learning, particularly in increasing the enthusiasm and interest in reading for elementary school students. This study aims to determine the effectiveness of utilizing Smart TV as a digital transformation medium in increasing students' interest in reading at MI Darun Najah, Srobyong, Mlonggo, Jepara. The method used is a descriptive qualitative case study approach, involving fourth and fifth grade students and class teachers as research subjects. Data collection was carried out through participatory observation, in-depth interviews, and documentation to obtain a more comprehensive picture of the application of Smart TV in learning activities. The results of the study indicate that the use of Smart TV can increase active student engagement in the learning process. Students are more motivated and interested in reading, thanks to the attractive visual display and interactive multimedia features. Smart TV also creates a more enjoyable learning atmosphere, by integrating various types of media, such as images, videos, and text, which support learning. However, several obstacles were also found, including limited mastery of technology by teachers and limited time for technology integration in daily learning. Therefore, this study recommends ongoing training for teachers in operating Smart TVs and the development of a more flexible digital technology-based curriculum to maximize the benefits of using Smart TVs in elementary school learning. The study also suggests the need for regular evaluation of the effectiveness of Smart TV use in improving students' literacy skills.